KNOWLEDGE AND ATTITUDE OF KINDERGARTEN TEACHERS ABOUT EARLY CHILDHOOD SEX EDUCATION - Mina Yumei Santi; Dea Surya Lakshita; Siti Tyastuti; Wafi Nur Muslihatun (Kesmas Indonesia, 2022)
Cases of child abuse in the last few years have occurred in Indonesia. Cases of violence that afflict early childhood are caused by several factors, one of which is the lack of sex education in early childhood. An understanding of the knowledge and availability of educators' skills is needed to start the application of sex education. The aims of this research is to find out the relationship between knowledge and attitudes about early childhood sex education in kindergarten teachers. Research method is an observational analytic cross sectional. The study was carried out in 2019. Total sample of kindergarten teacher research was 41 teachers in Pakualaman Yogyakarta, Special Region of Yogyakarta Province. Data analysis using chi-square test. The results of this research are the majority of teachers' knowledge is good (59.1%) with the majority of attitudes are not supportive (61.4%) which means that the respondent does not have the willingness to provide knowledge about sex education to kindergarten students. Most of the respondents were in the age range beetween 41 to 60 years (63.6%), higher education (93.2%) with non early childhood education undergraduate qualifications (50%), the media often used to obtain information about sex education was electronic media (77.3%) that is by using the internet (47.7%). Relationship between knowledge and attitudes teacher about early childhood sex education. The level of good knowledge has an opportunity of 5.833 times to support the provision of early childhood sex education.